Effect of Breed on Plasma Endothelin‐1 Concentration, Plasma Renin Activity, and Serum Cortisol Concentration in Healthy Dogs. (27th January 2016) - Höglund, K.; Lequarré, A.‐S.; Ljungvall, I.; Mc Entee, K.; Merveille, A.‐C.; Wiberg, M.; Gouni, V.; Lundgren Willesen, J.; Hanås, S.; Wess, G.; Mejer Sørensen, L.; Tiret, L.; et al.
Abstract : Background: There are breed differences in several blood variables in healthy dogs. Objective: Investigate breed variation in plasma endothelin‐1 (ET‐1) concentration, plasma renin activity, and serum cortisol concentration. Animals: Five‐hundred and thirty‐one healthy dogs of 9 breeds examined at 5 centers (2–4 breeds/center). Methods: Prospective observational study. Circulating concentrations of ET‐1 and cortisol, and renin activity, were measured using commercially available assays. Absence of organ‐related or systemic disease was ensured by thorough clinical investigations, including blood pressure measurement, echocardiography, ECG, blood and urine analysis. Results: Median ET‐1 concentration was 1.29 (interquartile range [IQR], 0.97–1.82) pg/mL, median cortisol concentration 46.0 (IQR, 29.0–80.8) nmol/L, and median renin activity 0.73 (IQR, 0.48–1.10) ng/mL/h in all dogs. Overall, breed differences were found in ET‐1 and cortisol concentrations, and renin activity ( P < .0001 for all). Pair‐wise comparisons between breeds differed in 67% of comparisons for ET‐1, 22% for cortisol, and 19% for renin activity, respectively. Within centers, breed differences were found at 5/5 centers for ET‐1, 4/5 centers for cortisol, and 2/5 centers for renin activity. Newfoundlands had highest median ET‐1 concentration, 3 times higher than Cavalier King Charles Spaniels, Doberman Pinschers, and Dachshunds. Median renin activity was highest in Dachshunds, twice the median value in Newfoundlands and Boxers. Median cortisol concentration was highest in Finnish Lapphunds, almost 3 times higher than in Boxers. Conclusions and Clinical Importance: Breed variation might be important to take into consideration when interpreting test results in clinical studies.